2001
DOI: 10.1074/jbc.m101756200
|View full text |Cite
|
Sign up to set email alerts
|

Two Phases of Chromatin Decondensation during Dedifferentiation of Plant Cells

Abstract: Cellular dedifferentiation is the major process underlying totipotency, regeneration, and formation of new stem cell lineages in multicellular organisms. In animals it is often associated with carcinogenesis. Here, we used tobacco protoplasts (plant cells devoid of cell wall) to study changes in chromatin structure in the course of dedifferentiation of mesophyll cells. Using flow cytometry and micrococcal nuclease analyses, we identified two phases of chromatin decondensation prior to entry of cells into S pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 144 publications
(81 citation statements)
references
References 28 publications
(29 reference statements)
2
79
0
Order By: Relevance
“…Interestingly, earlier findings showed that dedifferentiation of nuclei, chromatin decondensation and changes in density of nucleus staining took 72 -96 h, also in two distinct steps (Harikrishna et al 1989, Zhao et al 2001. In line with these steps the degradation of photosynthetic pigments and ultrastructural changes were observable, as well as the first accumulation steps of anthraquinone derivatives.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Interestingly, earlier findings showed that dedifferentiation of nuclei, chromatin decondensation and changes in density of nucleus staining took 72 -96 h, also in two distinct steps (Harikrishna et al 1989, Zhao et al 2001. In line with these steps the degradation of photosynthetic pigments and ultrastructural changes were observable, as well as the first accumulation steps of anthraquinone derivatives.…”
Section: Discussionmentioning
confidence: 82%
“…Middle lamella around the transfer cells turned into vesiculated and shiny coat. These structural changes might be related with the loss of original function and the isolation of cells entering cell cycle (Zhao et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, nuclei (75 l) were digested with increasing amounts (2, 5, and 10 units per 2 ϫ 10 6 nuclei) of micrococcal nuclease (MBI Fermentas) at room temperature for 12 min. A portion of the digested nuclei was used for DNA preparation as described (33). The remaining micrococcal nuclease (MNase)-digested nuclei were cooled on ice for 10 min before centrifugation at 13,000 ϫ g for 10 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…This also points to heterochromatin being a heterogeneous rather than a homogenous compartment, which can be specified not only by its level of compaction (33,50) but also by the molecular machinery involved in its formation.…”
Section: Figmentioning
confidence: 99%
“…Cell dedifferentiation was probably caused by reorganization of the chromatin structure, which altered gene expression patterns. Changes in this expression pattern lead to the formation of callus [8]. On the other hand, cytokinin plays a role in activating genes that are responsible for cell division [9].…”
Section: Resultsmentioning
confidence: 99%